RISK MANAGEMENT IN BANKING: THEORETICAL AND PRACTICAL ASPECTS - Sabirova Rysty Kuandikovna; Utepkalieva Kansulu Musaevna; Baimukhasheva Manchuk Konysbaevna; Zhumalieva Dinara (Academic Journal of Physical and Chemical Sciences, 2020)
The basis of bank risk management is the neutralization of their negative consequences for the bank’s activity in the event of a possible risk event. At the same time, the bank’s costs of neutralizing the corresponding banking risk should not exceed the amount of possible bank losses on it, even at the highest probability of neutralizing their negative consequences in the event of a probable risk event. At the same time, the implementation of the relevant banking operation may be dictated by the requirements of the strategy and focus of banking activities. Management of risks initiated by banks can significantly strengthen the client position of banking management and provide a synergistic effect of balancing the formation of qualitative characteristics of banking products. The globalization of financial markets, information technology development, and increasing competition have largely affected bank business and its risk management. Together with these forces, regulatory factors play a significant role. This chapter approaches bank risk management under the regulators’ perspective with an emphasis on the risk-based capital regulation. Specifically, how bank risk is regulated under the risk-based capital regulation and whether the regulation shapes bank risk are discussed in detail. In such a way, the chapter provides better understanding of the risk-based capital regulation and bank risk-taking behaviors.